Embriologia de Pera glabrata (Schott) Poepp. ex Baill. (Peraceae, Malpighiales) - Franca, Rafael de Oliveira (2015)
Pera is a neotropical genus, currently belonging to Peraceae family. These circumscription was the result of inclusion of Rafflesiaceae family between the old Pereae tribe and all other Euphorbiaceae, wherein Pereae was elevated to the family becoming Euphorbiaceae monophyletic again. These changes were not well accepted because Rafflesiaceae are holoparasitic with extremely reduced vegetative body and large flowers, while Peraceae and Euphorbiaceae have well developed vegetative parts and reduced flowers. As the embryology of Peraceae was unknown and embryological processes are conservative and have been used to solve taxonomic problems at different hierarchical levels, we studied the embryology of Pera glabrata searching for similarities between Peraceae, Rafflesiaceae, and Euphorbiaceae that support such grouping. The current circumscription of the clade was not supported by embryology, suggesting a rapprochement between Peraceae and Euphorbiaceae. Were also listed possible synapomorphies for Peraceae, including the epidermis of anther with two cell types that had not yet been described for other angiosperm. The presence of placental obturator in Pera appears as a possible synapomorphy for the Ixonanthaceae, Linaceae, Phyllanthaceae, Picrodendraceae, Peraceae and Euphorbiaceae families.